2017
DOI: 10.1002/cpp.2068
|View full text |Cite
|
Sign up to set email alerts
|

Indirect exposure to client trauma and the impact on trainee clinical psychologists: Secondary traumatic stress or vicarious traumatization?

Abstract: The results, discussions, and conclusions presented herein are identical to those in the printed version. This electronic version of the thesis has been edited solely to ensure conformance with copyright legislation and all excisions are noted in the text. The final awarded and examined version is available for consultation via the University Library.ii Declaration This work has not been submitted for any other degree or to any other institution.iii Structure and word counts Literature Review 8000References 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
44
1
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 53 publications
4
44
1
5
Order By: Relevance
“…According to Figley's (1995) definition, a therapist suffering STS would likely report that they were experiencing symptoms of avoidance, numbing, and hyperarousal. VT involves 'disrupted beliefs in relation to the self, others, and the world from cumulative exposure to client trauma narratives, in addition to trauma symptoms (Makadia, Sabin-Farrell, & Turpin, 2017, p. 1060McCann & Pearlman, 1990). Taken together, both STS and VT are consistent with some (although certainly not all) of the specifiers of a diagnosis of PTSD.…”
supporting
confidence: 54%
See 3 more Smart Citations
“…According to Figley's (1995) definition, a therapist suffering STS would likely report that they were experiencing symptoms of avoidance, numbing, and hyperarousal. VT involves 'disrupted beliefs in relation to the self, others, and the world from cumulative exposure to client trauma narratives, in addition to trauma symptoms (Makadia, Sabin-Farrell, & Turpin, 2017, p. 1060McCann & Pearlman, 1990). Taken together, both STS and VT are consistent with some (although certainly not all) of the specifiers of a diagnosis of PTSD.…”
supporting
confidence: 54%
“…Baum, 2016), age, personal trauma history (see also Dagan, Ben-Porat, & Itzhaky, 2016), fewer years of trauma-informed training, fewer years in the field, poorer coping behaviour, and reduced social and supervisory support (Makadia et al, 2017). Recent Israeli studies, however, have found inconsistent mediators of resiliency in relation to VT and STS.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Burnout involves a feeling of being emotionally drained, a sense of detachment towards the recipients of one’s care and a plummeting sense of competence [ 15 ]. Studies have highlighted moderate to high rates of burnout and secondary traumatic stress in mental health professionals such as clinical psychologists, counsellors, psychotherapists, psychiatric social workers and psychiatric nurses [ 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%